ETIKA KOMUNIKASI “AOK” - Arifin Hidayatullah; Iqrom Faldiansyah (Program Study of Islamic Communication and Broadcasting, Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2022)
This article aims to describe communication ethics using Analysis, Objectivity and Creativity (AOK) as a solution to discrimination on social media using an Islamic perspective. Analysis is an investigation related to problems in order to find out the existing reality by drawing tentative assumptions through study and seeking the truth. In an Islamic perspective, the importance of analyzing information has been explained in Q.S Al-Hujarat (49) verse 6. Objectivity which contains the connection of language and logic in studying something so that it can be viewed openly and tested for truth is mentioned in Q.S At-Taubah (9) paragraph 119 which classifies honesty is not just an attitude, but a virtue of nobility that must be upheld. While creativity is about the ability to come up with an idea or modify something that already exists into a new idea concept through aspects of analysis and objectivity in solving a problem as seen from Q.S Ar-Ra'ad (13) verse 11.